Adolescents’ Social Networks: Exploring Different Patterns of Socio-Digital Participation - Shupin Li; Lauri Hietajärvi; Tuire Palonen; Katariina Salmela-Aro; Kai Hakkarainen (Routledge, Taylor & Francis Group, 2022)
The purpose of the study was to assess adolescents’ participation in various socio-digital activities by using a self-report questionnaire, a social networking questionnaire and interviews. The participants (N=253) were grade 6-9 students from a multicultural lower secondary school in Finland. Three profiles of socio-digital participation were identified: friendship oriented basic participators (n=161), gaming-oriented participators (n=61) and creative participators (n=31) intensively engaged in diverse socio-digital practices. The analyses revealed systematic differences in social networking relations as a function of adolescents’ social-digital participation profile and gender. The reciprocal values in hanging out, liking and media multiplexity were highest for creative participators whereas gaming-oriented participators were less socially active than their peers. Socio-digital expertise of creative participators was socially recognized by larger group of peers than that of the other groups. The study produces methodological tools suitable for collecting systematic longitudinal data of socio-digital practices of larger groups of adolescents in future.